2021
DOI: 10.1007/s00259-021-05246-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of amyloid-PET and tau-PET: a head-to-head comparison

Abstract: Purpose Assess the individual and combined diagnostic value of amyloid-PET and tau-PET in a memory clinic population. Methods Clinical reports of 136 patients were randomly assigned to two diagnostic pathways: AMY-TAU, amyloid-PET is presented before tau-PET; and TAU-AMY, tau-PET is presented before amyloid-PET. Two neurologists independently assessed all reports with a balanced randomized design, and expressed etiological diagnosis and diagnostic confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…However, when the focus switched from the theoretical belief to the perceived clinical utility of PET scans assessing amyloid and tau, responders did not show a clear preference for amyloid-PET. Consistently, a recent work assessing the diagnostic value of amyloid-PET and tau-PET in a memory clinic population, showed that the two exams signi cantly impacted diagnosis and diagnostic con dence in a similar way [4]. Notably, clinicians and biomarker experts proved to be perfectly aligned both with regard to beliefs on the pathogenic role of amyloid and tau and to the perceived clinical utility of amyloid-PET and tau-PET.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, when the focus switched from the theoretical belief to the perceived clinical utility of PET scans assessing amyloid and tau, responders did not show a clear preference for amyloid-PET. Consistently, a recent work assessing the diagnostic value of amyloid-PET and tau-PET in a memory clinic population, showed that the two exams signi cantly impacted diagnosis and diagnostic con dence in a similar way [4]. Notably, clinicians and biomarker experts proved to be perfectly aligned both with regard to beliefs on the pathogenic role of amyloid and tau and to the perceived clinical utility of amyloid-PET and tau-PET.…”
Section: Discussionsupporting
confidence: 54%
“…Their use will probably increase as new effective therapies will become available. It must be remarked that the frequency of use of each biomarker is clearly in uenced by its local availability, which varies signi cantly from center to center with MRI being already widely available and tau-PET being available only in research contexts, despite the promising preliminary results exhibited since its recent introduction [4,17]. Of note, the limited frequency of use detected for amyloid-PET and tau-PET might be in uenced by the lack of reimbursement for this examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies state that the main value of A␤-PET on a group level is the high negative predictive value [5][6][7]. However, research groups have recently assessed the usefulness of A␤-PET imaging, demonstrating its value in terms of change in diagnosis [8,9] and management [10].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies should namely measure the incremental diagnostic value provided by a test, i.e., not only its diagnostic performance but also its added value when other information, for example the result of gateway or other tests, is already available. There are only a few diagnostic studies measuring this parameter [10][11][12], one in this issue comparing the incremental diagnostic value of amyloid PET and tau PET [13]. The limited evidence on the comparison and combination of biomarkers presumably contributes to explain the variable policies for coverage across countries and the lack of widely accepted detailed diagnostic algorithms [1,2].…”
mentioning
confidence: 99%